Dynamics of Audit Lag-Board of Directors and Audit Committees' Effect' - Assaker, Guy (2015)
Audit procedures are considered to be an external governance mechanism tool used by shareholders from an agency theory perspective. The empirical model is constructed to assess the theoretical and statistical relationship between audit lag and corporate governance characteristics over a period of four years (for FTSE 350 companies excluding financial institutions between 2007 and 2010). This paper studies the effect of corporate governance mechanisms, board of directors and audit committee, on audit report lag. The importance of this research comes from the few studies conducted regarding the relationship between corporate governance and audit report lag. It is crucial to understand the determinants o